“ELSA SPEAK” IN AN ONLINE PRONUNCIATION CLASS: STUDENTS’ VOICES - Rolisda Yosintha; Agnira Rekha (IJEE (Indonesian Journal of English Education), 2022)
ABSTRACTDeveloping productive skills such as pronunciation requires more than just comprehension. Students should have ample opportunities to practice their knowledge. With the strike of Covid-19 that has abruptly shifted learning from offline to an online setting, lecturers have tried to employ technologies such as Elsa Speak in teaching pronunciation online. With the rising popularity of this application, there should be a study investigating how the students perceive Elsa Speak in online pronunciation learning. To do so, this present study employed a mixed-method approach to know the attitudes of 112 English Department students toward Elsa Speak used in their online pronunciation class. Through an analysis of data collected from questionnaires and interviews, the study found that most participants had a positive attitude toward Elsa Speak concerning its use in their online pronunciation class. Even though there were some negative comments from the participants, the benefits outweighed the downside. To make the integration of Elsa Speak into online pronunciation learning more accommodating to students’ needs, lecturers could take some pedagogical measures, such as supplementing the materials provided by Elsa Speak with those from other resources, increasing their involvement during the learning process, and promoting collaborative activities. ABSTRAKMengembangkan keterampilan produktif seperti pengucapan membutuhkan lebih dari sekedar pemahaman. Siswa harus diberi banyak kesempatan untuk mempraktikkan pengetahuan mereka. Dengan adanya wabah Covid-19 yang mengubah sistem pembelajaran dari luring ke daring, dosen menggunakan teknologi seperti Elsa Speak dalam mengajar mata kuliah pengucapan secara daring. Dengan meningkatnya popularitas dari aplikasi ini, harus ada penelitian yang menyelidiki bagaimana persepsi siswa tentang Elsa Speak dalam pembelajaran pengucapan secara daring. Penelitian ini menggunakan pendekatan metode campuran untuk mengetahui sikap 112 mahasiswa Jurusan Bahasa Inggris terhadap Elsa Speak yang digunakan di kelas pengucapan daring mereka. Melalui analisis data yang dikumpulkan dari kuesioner dan wawancara, peneliti menemukan bahwa sebagian besar mahasiswa memiliki sikap positif terhadap Elsa Speak terkait penggunaannya di kelas mereka. Meskipun terdapat beberapa komentar negatif dari partisipan, manfaat Elsa Speak lebih besar daripada kerugian yang ditimbulkan. Supaya integrasi Elsa Speak ke dalam pembelajaran pengucapan secara daring lebih mengakomodasi kebutuhan mahasiswa, dosen dapat mengambil beberapa langkah pedagogis, seperti menggunakan materi tambahan untuk memberi variasi terhadap materi yang disediakan oleh Elsa Speak, meningkatkan keterlibatan dosen selama proses pembelajaran, dan mengimplementasikan kegiatan pembelajaran yang kolaboratif.